REVIEW OF ACTION ON FOREIGN WHO ILLEGAL FISHING IN TAREMPA IMMIGRATION OFFICE AREA - Renra Hata Galih (Jurnal Ilmiah Kajian Keimigrasian, 2021)
Illegal fishing, namely fishing activities by foreign people or vessels in waters that are the jurisdiction of a country, without permission from that country, or contrary to laws and regulations. The problem of Illegal fishing not only causes problems regarding Indonesia's natural resources but also raises various immigration problems from the initial detention until the perpetrators of illegal fishing are deported to their home countries. The process of Immigration Administration Action (TAK) causes a lot of costs to be incurred, therefore simplification of the Immigration Analyst Actions (TAK) process and new detention methods will reduce costs incurred in the process of managing illegal fishing actors.